Prevalence And Risk Factors Of Work-Related Musculoskeletal Disorders Amongst Nurses In Hospital Sultan Abdul Halim, Kedah, Malaysia - Krishnan, K.Saraswathi (2022)
A nursing career is considered one of the most physically labourious professions. It is associated with a high prevalence of Work-related Musculoskeletal Disorders (WRMSDs). WRMSDs constitute a major problem in many countries, resulting in substantial costs and impact on the quality of life. This study aimed to estimate the prevalence and risk factors of MSDs-related pain in various anatomical regions among nurses. A cross-sectional study involving 300 conveniently sampled registered nurses with clinical experience at Sultan Abdul Halim Hospital, Kedah was conducted using a self-administered questionnaire.